Gauge Theories in Particle Physics: A Practical Introduction, Volume 1 From Relativistic Quantum Mechanics to QED, Fourth Edition - Aitchison, Ian J R (Taylor & Francis, 2013)
Volume 1 of this revised and updated edition provides an accessible and practical introduction to the first gauge theory included in the Standard Model of particle physics: quantum electrodynamics (QED).The book includes self-contained presentations of electromagnetism as a gauge theory as well as relativistic quantum mechanics. It provides a uniqu